(untitled) (Research, Society and Development, 2021)
Objective: To analyze there notified cases of gestational syphilis in the Health District VII, Recife, Brasil. Method: This is a documentary study, exploratory-descriptive, carried out through the notification forms of cases of gestational syphilis, which occurred in the period be tween January 2014 and December 2018, analyzed from descriptive statistics. Results: 247 cases were identified during the analysis period, with a higher in crease in 2018. The women were bet ween 20 and 24 year sold, had low education, were brown, and had a diagnosis in the second and third trimester of pregnancy. There were no significant differences in the profile of pregnant women over the years. Conclusion: The increasing number of cases showed a weakness in health services during the process, demonstrating the need to encourage notification and correct completion of the forms. There fore, we emphasize the importance of health education, in order to clarify the main points related to the disease, using a language that is easy for the population to understand.